Attracting and Retaining Local Talent : A Swedish University Perspective - Näppä, Anna; Hertzman, Josefina (2011)
In the world of today, destinations like cities are encouraged to think more like companies. Branding is not only for commercial products and companies, but even for destinations. Especially tourism destinations have long felt the need to differentiate themselves from each others, but it is equally important in resident retention. Cities with universities get new residents yearly, but these students often leave after graduating, and some cities have reacted to this. The purpose of this thesis is to provide a better understanding on how city branding is being used to attract and retain university students in Sweden. For this thesis a case study was chosen and four university students were interviewed and Luleå was used as the reference city. The data suggests that cities would gain great benefits from branding towards university students, such as new knowledge and innovation, new investment, flow of workers into local companies and student retention. Cities need to work on branding activities that build relationships to the residents, and in the case of university students the time is limited and the effort must come from the start. In order to reach out to the students, a marketing strategy must be conducted. When it comes to urban development shopping and nightlife are two important aspects to consider, and there needs to be life to the city to keep the students excited. Furthermore, social medias should be utilized more for promotional efforts, together with public relations and events. Validerat; 20110613 (anonymous)